An evidence base to optimise methods for involving patient and public contributors in clinical trials: a mixed-methods study - Carrol Gamble; Louise Dudley; Alison Allam; Philip Bell; Deborah Buck; Heather Goodare; Bec Hanley; Jennifer Preston; Alison Walker; Paula R Williamson; Bridget Young (National Institute for Health Research, 2015)
Background: In comparison with other study designs, randomised trials are regarded as particularly likely to benefit from patient and public involvement (PPI). Using mixed-methods research we investigated PPI from the perspectives of researchers and PPI contributors. Methods: Randomised trials in receipt of funding from the Health Technology Assessment (HTA) programme between 2006 and 2010 were identified. Funding applications and board and referee comments were obtained and data relevant to PPI extracted. Chief investigators (CIs), PPI contributors and UK Clinical Research Collaboration Registered Clinical Trials Units (RCTUs) were surveyed. Interviews were conducted with researchers and PPI contributors. Results: A total of 111 trials were included. Text relevant to PPI was identified in half of the trials for which the first-stage applications were available, but only one-quarter described PPI within their development. In the second stage of the application, the majority provided some text relevant to PPI, with over half having PPI in their development. Fewer than half of referees commented on PPI, and funding boards rarely provided comments in relation to PPI. Seventy-three per cent (81 of 111) of CIs responded to the survey and 98% (79 of 81) included PPI at some stage in their trial. CIs considered high impact from PPI contributors to occur more frequently in trial setup, with low or no impact being more common during trial conduct, analysis and dissemination. Only one-third of CIs provided PPI contributor contact details but all contributors contacted completed the survey. The majority of contributors felt engaged and valued by the research team. Interviews were conducted with researchers and/or PPI contributors for 28 trials identifying two main influences on perception of PPI impact: whether or not CIs expressed personal goals and plans for PPI; and the quality of their relationship with the PPI contributors. The importance of early engagement was identified, with opportunity for input thereafter limited. Three PPI roles were identified: oversight, managerial and responsive. Oversight roles, as required by funders, were associated with low impact in comparison with responsive or managerial roles. Most researchers could see some value in PPI training for researchers, although those that had received such training themselves expressed concerns about its purpose and evidence base. Training for PPI contributors was considered unnecessary, with conversational approaches preferred, although this did not appear to provide an opportunity for role negotiation. The RCTU survey response rate was 85% (39 of 46). The majority (37 of 39) reported PPI within trials co-ordinated by their unit. Trial characteristics were used by half to determine the approach to PPI. Two-thirds reported recent developments or changes in implementing plans for PPI (21 of 33). Support to PPI contributors was commonly offered through members of staff at the unit. Conclusions: PPI is occurring in the majority of trials funded by the HTA programme, but uncertainty remains about how it is assessed and valued. Early involvement, building a relationship between researchers and contributors, responsive or managerial roles, and having defined goals for PPI were associated with impact. Efficiency could be gained by utilising the RCTU network to identify and tackle challenges, and develop a risk-based approach utilising trial characteristics. Recommendations are made to trial funders and the research community. Given the difficulties for some informants in recalling PPI contributions, future research using a prospective approach would be valuable. Ethnographic research that combines observation and multi-informant interviews is likely to be informative in identifying impact. The research community needs to give further consideration to processes for selecting PPI contributors and models of implementing PPI. Funding: The National Institute for Health Research Health Services and Delivery Research programme and INVOLVE.